2022
DOI: 10.3389/fonc.2022.781270
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Peptides/Proteins Encoded by circRNA: An Update on Mechanisms and Functions in Human Cancers

Abstract: The discovery of circular RNAs and exploration of their biological functions are increasingly attracting attention in cell bio-sciences. Owing to their unique characteristics of being highly conserved, having a relatively longer half-life, and involvement in RNA maturation, transportation, epigenetic regulation, and transcription of genes, it has been accepted that circRNAs play critical roles in the variety of cellular processes. One of the critical importance of these circRNAs is the presence of small open r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 145 publications
(177 reference statements)
0
5
0
Order By: Relevance
“…It is worth mentioning although, circRNAs were initially thought to function as non-coding RNAs, recent evidence has shown that some circRNAs can encode proteins ( 135 , 136 ) These proteins are synthesized through different mechanism and are typically smaller than canonical proteins ( 130 ). The mechanism of protein coding by circRNAs is still an area of active research and is not completely understood.…”
Section: Noncoding Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning although, circRNAs were initially thought to function as non-coding RNAs, recent evidence has shown that some circRNAs can encode proteins ( 135 , 136 ) These proteins are synthesized through different mechanism and are typically smaller than canonical proteins ( 130 ). The mechanism of protein coding by circRNAs is still an area of active research and is not completely understood.…”
Section: Noncoding Rnasmentioning
confidence: 99%
“…Cap-independent translation Initiation: this method allows them to bypass the traditional mechanism of translation initiation that requires a 5’ cap structure ( 135 ) and can occur through various mechanisms, such as internal ribosome entry sites (IRES) or N6-methyladenosine (m6A) modifications ( 136 ).…”
Section: Noncoding Rnasmentioning
confidence: 99%
“…[26][27][28][29] CircRNAs are essential in the occurrence and progression of malignant tumors. [30][31][32] For example, circSATB2 was highly expressed in the serum secretions of lung cancer patients, with high sensitivity and specificity for clinical detection. It was also associated with the proliferation, migration, and invasion of lung cancer cells, [33] indicating that circSATB2 might be a promising biomarker for diagnosing lung cancer.…”
Section: Silencing Hsa_circ_0015326 Promotes Apoptosis Of Ovarian Can...mentioning
confidence: 99%
“…In addition, circular RNAs (circRNAs), a class of highly abundant and evolutionary conserved ncRNAs, are covalently closed RNA molecules that lacks free 3′ and 5′ ends and have recently been identified as functional RNA molecules [ 8 , 9 ]. In addition to their regulatory roles as noncoding transcripts, evidence has recognized that a small portion of lncRNAs and circRNAs contain short open reading frames (sORFs) that can be translated into functional small peptides [ 10 ].…”
Section: The Noncoding Rna Transcriptome In Pulmonary Hypertensionmentioning
confidence: 99%